1998
DOI: 10.1016/s0895-7061(98)00161-7
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hypotension: evaluation by ambulatory blood pressure monitoring☆

Abstract: To elucidate whether postprandial hypotension (PPH) is associated with any diurnal change of blood pressure, ambulatory blood pressure monitoring was performed on 121 hospitalized essential hypertensive patients who received standardized meals. Postprandial change in blood pressure was defined as the difference between mean systolic blood pressure (SBP) 1 h before and 2 h after each meal. The postprandial decline of SBP showed age-dependent augmentation. The degree of PPH was significantly related to the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
3
35
2
2
Order By: Relevance
“…Other than these 2 studies, there are several previous reports on a blood pressure reduction by breakfast intake. [23][24][25] This effect of breakfast intake on blood pressure in the morning might be one of the mechanisms of the result from the present study. Because we considered hypertension as a major mediator between breakfast intake and stroke, especially cerebral hemorrhage, we conducted further analyses after stratification by medication use of hypertension.…”
Section: Discussionsupporting
confidence: 52%
“…Other than these 2 studies, there are several previous reports on a blood pressure reduction by breakfast intake. [23][24][25] This effect of breakfast intake on blood pressure in the morning might be one of the mechanisms of the result from the present study. Because we considered hypertension as a major mediator between breakfast intake and stroke, especially cerebral hemorrhage, we conducted further analyses after stratification by medication use of hypertension.…”
Section: Discussionsupporting
confidence: 52%
“…Blood pressure (BP) was measured every 30 min from 6:00 AM to 10:00 PM and every 60 min from 10:00 PM to 6:00 AM of the following day (17).…”
Section: Twenty Four-hour Blood Pressure Determinationmentioning
confidence: 99%
“…14 However, only a few studies have investigated the effect of PPH on the diurnal change in BP in hypertensive patients. 15,16 In our previous study, 16 we evaluated PPH with ambulatory BP monitoring (ABPM) and showed that PPH contributed to the variability of BP in the daytime and the morning surge of BP, independent of the dipper and nondipper phenomena. Clinically, PPH can cause light-headedness, fainting, falls, or even transient ischemic attack.…”
mentioning
confidence: 99%